Alteration in hormonal level and testicular histomorphology in rats treated with alcohol (ALC) and cannabinol (CBN) (2019)
This study explores the effects of chronic alcohol and cannabinol exposure on the testosterone levels and the histomorphological integrity/cytoarchitecture of the rats’ testes. Adults male Wistar rats were randomly divided into control (distilled water), methanol (2mg/kg bw), alcohol (3g/kg bw), cannabinol (10mg/kg bw) and alcohol (3g/kg bw) plus cannabinol (10mg/kg bw) groups respectively. Alcohol and cannabinol were administered orally twice daily for 52 days (spermatogenic cycle in rats) and at the end of treatment, male reproductive organ (testis) was removed and cleared of adherent tissue and then fixed for histological examination. Blood samples were collected via retro-orbital sinus for hormone (testosterone) assay. Serum testosterone levels were measured using the enzyme immunoassay (E.I.A.) technique. Hormonal assay showed significant reductions in the levels of testosterone (T) (p < 0.05) in the alcohol alone, cannabinol alone and in the alcohol plus cannabinol treated groups. The Histological analysis of the treated groups showed severe reduction of the spermatogenic cells. The present study showed that following chronic alcohol and/or cannabinol administration the results showed significant reduction (p<0.05) in testosterone levels and a detrimental effect on the histomorphology of the testes. Alcohol and/or cannabinol therefore exhibit inhibitory effects causing inhibition of testosterone as observed in this study.